2015
DOI: 10.1172/jci76765
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α/XBP1-mediated branch of the unfolded protein response regulates osteoclastogenesis

Abstract: (T. Tohmonda).lowed by Alexa Fluor 488-conjugated anti-rabbit IgG (Invitrogen); nuclei were counterstained with DAPI. Images of the cells were acquired with Olympus DP controller software via an Olympus DP70 camera mounted on an Olympus IX71 microscope at room temperature. The objective was a ×100 APO/1.65 NA lens. Images were processed with Adobe Photoshop CS6 for contrast correction and to generate merged images.Statistics. All statistical analyses were performed using Prism 6 (GraphPad Software). Two-tailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 55 publications
1
52
0
Order By: Relevance
“…Interestingly, although ROS and UPR have certain damage to normal cells, both of them are crucial factors that drive osteoclast differentiation and bone resorption 37,38 . Rac‐Nox1/2/4 and IRE1α/XBP1 are the key signaling pathways for regulating ROS and UPR, respectively; and the reason why ROS and UPR have different roles in other cell types and osteoclasts is also associated with these two pathways playing important roles in osteoclastogenesis 12,39,40 . The protective effects of ThDP in most cell types by inhibiting ROS accumulation and UPR signaling turned out to be suppressive in RANKL‐induced osteoclast differentiation and formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although ROS and UPR have certain damage to normal cells, both of them are crucial factors that drive osteoclast differentiation and bone resorption 37,38 . Rac‐Nox1/2/4 and IRE1α/XBP1 are the key signaling pathways for regulating ROS and UPR, respectively; and the reason why ROS and UPR have different roles in other cell types and osteoclasts is also associated with these two pathways playing important roles in osteoclastogenesis 12,39,40 . The protective effects of ThDP in most cell types by inhibiting ROS accumulation and UPR signaling turned out to be suppressive in RANKL‐induced osteoclast differentiation and formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies started to recognized the significance of unfolded protein response (UPR) and endoplasmic reticulum (ER) stress related signaling in the process of physical osteoclast differentiation. The intracellular inositol‐requiring protein‐1α/X‐box‐binding protein (IRE1α/XBP1) pathway that originally integrates UPR has been found necessary in osteoclast differentiation 12 . Furthermore, ER stress mediated eukaryotic initiation factor 2α phosphorylation and downstream activating transcription factor 4 have been demonstrated playing a direct role in regulating osteoclastogenesis 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we consistently observed a UPR‐induced increase in RANKL expression in osteoblast and osteocyte cell lines, cultured neonatal calvaria, calvaria‐derived osteoblasts, and marrow‐free cortical bone preparations. It was previously reported that an increase in UPR is involved in RANKL‐stimulated osteoclastogenesis . Thus, Tm‐induced resorption observed in bone organ cultures and Tm‐induced increase in osteoclast number in mice could be due, in part, to increased UPR in these cells.…”
Section: Discussionmentioning
confidence: 88%
“…It was previously reported that an increase in UPR is involved in RANKL-stimulated osteoclastogenesis. 66 Thus, Tm-induced resorption observed in bone organ cultures and Tm-induced increase in osteoclast number in mice could be due, in part, to increased UPR in these cells. Elevated UPR has been associated with increased osteoclasts and bone loss in a rats with osteonecrosis of the femoral head, 67 mice with periodontitis induced by in P gingivalis, 68 as well as mouse models of hind limb unloading and particle-induced osteolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Primary osteoblasts were harvested from the calvaria of newborn mice as described previously. 27 For primary osteoclast culture, bone marrowederived macrophages were prepared as previously described 28 and used as osteoclast precursors. They were cultured in the presence of 50 ng/mL soluble receptor activator of NF-kB ligand and 3.3 Â 10 3 U/mL macrophageecolony stimulating factor for 5 days to induce osteoclastogenesis.…”
Section: Generation Of Hybid-deficient Micementioning
confidence: 99%